2011
DOI: 10.1111/j.1365-2125.2011.03914.x
|View full text |Cite
|
Sign up to set email alerts
|

A new topical formulation enhances relative diclofenac bioavailability in healthy male subjects

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Therapy with topical non‐steroidal anti‐inflammatory drugs (NSAIDs) relies on the ability of the active drug to penetrate the skin in sufficiently high amounts to exert a clinical effect, which is linked to the specific galenic properties of the formulation. WHAT THIS STUDY ADDS • This phase 1 study characterizes the transdermal penetration and plasma exposure of different dose levels with galenic differences of a novel topical diclofenac formulation under developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…As illustrated in the present study, differences in the compositions of topical diclofenac formulations have been shown to be the primary determinants of differences in the rate of transdermal drug delivery (Brunner et al, ; Escribano et al, ; Folzer et al, ; Nivsarkar et al, ). For example, Escribano et al () compared the ex vivo human skin permeation of four distinct formulations of diclofenac sodium, including one microemulsion formulation.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…As illustrated in the present study, differences in the compositions of topical diclofenac formulations have been shown to be the primary determinants of differences in the rate of transdermal drug delivery (Brunner et al, ; Escribano et al, ; Folzer et al, ; Nivsarkar et al, ). For example, Escribano et al () compared the ex vivo human skin permeation of four distinct formulations of diclofenac sodium, including one microemulsion formulation.…”
Section: Discussionmentioning
confidence: 64%
“…Okuyama et al reported that adding diisopropyl adipate, which is a component of the present hydrogel formulation, to a diclofenac alcohol gel synergistically enhanced the in vivo absorption of diclofenac in guinea‐pigs as shown by plasma AUC and by underlying muscle concentrations (Okuyama et al, ). Others have reported that formulating diclofenac as an acid rather than as a salt may enhance the transdermal absorption compared with diclofenac emulsion gel (Brunner et al, ). In addition, small differences in ex vivo transdermal permeation rates have been reported for different salts of diclofenac when tested in simple solutions (Minghetti, et al, ), but whether these differences occur in complex transdermal formulations has not been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was an observational study, and the sample size was determined based on previous pharmacological studies using CEUS or functional MRI for monitoring of renal perfusion as well as pharmacological studies on topical diclofenac application . In the mentioned work by Getzin et al ., a power calculation was performed for different scenarios with small pharmacological effects on renal perfusion.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, topical diclofenac administration is frequently discussed as an alternative for patients at risk of adverse drug events, since it might have less systemic side effects . Nonetheless, some preparations of topical diclofenac have been reported to reach measurable plasma concentrations after repeated application …”
Section: Introductionmentioning
confidence: 99%